Upaya Penanganan Tinea Corporis dan Obesitas Grade II pada Pasien Perempuan Usia 50 Tahun melalui Pendekatan Kedokteran Keluarga di Puskesmas Nisam Kabupaten Aceh Utara - Yolanda Agtari; Noviana Zara (Journal of Medical Practice and Research, 2026)
Tinea corporis represents a common superficial dermatophyte infection in tropical regions, often exacerbated by behavioral, environmental, and metabolic risk factors. This study aimed to comprehensively analyze the management of tinea corporis with grade II obesity in a 50-year-old female patient using a family medicine approach at a primary healthcare facility. The study employed an empirical descriptive case report design integrating clinical findings, structured anamnesis, physical examination, and home visit assessment to identify multidimensional determinants of disease. Results demonstrated chronic pruritic annular lesions with characteristic scaling and central healing, supported by stable vital signs and absence of systemic involvement. Behavioral factors such as habitual scratching, shared personal items, and limited health literacy were identified alongside environmental contributors including household density. Obesity further influenced disease persistence through increased skin moisture. A comprehensive intervention combining antifungal therapy and family-based education improved disease management outcomes. The findings highlight the importance of integrating clinical, behavioral, and familial dimensions to enhance therapeutic effectiveness. The family medicine approach provides a strategic framework for addressing chronic dermatological conditions through holistic, patient-centered care.